Proposal of a Classification of Analogies - Alvargonzález, David (Informal Logic)

(untitled) (Informal Logic, 2020)
In this paper, I will propose a classification of analogies based on their internal structure. Selecting the criteria used in that classification first requires discussing the minimal constitutive parts of any analogy. Accordingly, I will discuss the differences between analogy and similarity and between analogy and “synalogy,” and I will stress the importance of the analogy of operations and procedures. Finally, I will set forth a classification of the different types of analogies, which lends itself to a further understanding of the differences between certain modulations of the general idea of analogy, such as archetypes, prototypes, models, simulations, parables, paradigms, canons, maps, thought experiments, myths, utopias, dystopias and fables.